Judith M. Barringer, Olympia. A Cultural History. - Cartledge , Paul (Journal of Greek Archaeology, 2024)
When the modern iterations of the Summer Olympics come round, there is often detectable a string of publications, more and less scholarly, on the ancient (summer-only) quadrennial Games and their original, unique and immovable, site. Professor Barringer’s severely scholarly and academic volume is no exception, if only by accident. It first appeared in the same year that the Tokyo Olympics (officially XXXII) actually occurred, though – thanks to the covid-19 pandemic – that was not the year for which they had been scheduled. The ancient version of the Games lasted for over 1100 years without a single break (give or take a couple of reorganizations and Emperor Nero’s gross interference in CE 66/67), but celebrations of the modern version running since 1896 have been either totally omitted several times (1916, 1940, 1944) or (2020) postponed. That very fact should give rise to the thought that maybe the modern Olympics really aren’t very much like the ancient, notwithstanding the wishes and claims of its founding father, Pierre Baron de Coubertin (1863-1937).